Optimizing light sources for selective growth of purple bacteria and efficient formation of value-added products. (20th January 2021) - Yu, Siwei; Peng, Lai; Xu, Yifeng; Song, Shaoxian; Xie, Guo-Jun; Liu, Yiwen; Ni, Bing-Jie
Abstract: The slow growth and inefficient productivity of value-added products are the main obstacles to industrialization of purple non-sulfur bacteria (PNSB)-based technology for clean production from wastewater. To overcome these, a strain of PNSB was obtained through selective cultivation and purification, which was subsequently identified as Rhodobacter sphaeroides . The impacts of different light sources (i.e. halogen lamp, incandescent lamp, infrared light, and light-emitting diodes (LEDs) of white, red, blue, green and yellow) were investigated on the production of biomass, pigments and protein by Rb. sphaeroides . Results suggested that, in addition to infrared light, green and yellow LED, most light sources managed to keep the purity of Rb. sphaeroides above 96%. After 7-day cultivation, halogen lamp and infrared light yielded the highest concentrations of biomass (5.78 g SS L −1 ) and pigments (22.6 mg L −1 ), respectively. Highest protein-to-biomass ratio (82%) was observed under blue LED, while maximum protein concentration (4.43 g protein L −1 ) was obtained under incandescent lamp. The infrared light and incandescent lamp might account for the higher production of pigments and protein, respectively. Considering the culture screening, productivity of biomass, pigments and protein as well as energy efficiency together, incandescent lamp was the optimal light source in lab scale. It also gave rise to the highest net profit of $ 14.43 per ton of wastewater treated in a desktop extrapolation evaluating economic benefit of full-scale PNSB-based wastewater recovery process. The results jointly demonstrated that appropriate light source (i.e. incandescent lamp) would boost the microbial protein production and enhance the protein content, which is of great importance to cost control in practice. Graphical abstract: Image 1 Highlights: Rb. sphaeroides contained culture were purified from water pond. Light sources affect biomass production and PNSB purity. Light sources affect pigments and protein production by PNSB. Incandescent lamp is the preferable light source.